1988
DOI: 10.1111/j.1474-8673.1988.tb00175.x
|View full text |Cite
|
Sign up to set email alerts
|

Two α‐adrenergic contractions with different Ca2+ activation mechanisms in response to field nerve stimulation in the circular smooth muscle of guinea‐pig vas deferens

Abstract: 1. Two noradrenergic components of contraction were induced by field nerve stimulation of the circular smooth muscle of guinea-pig vas deferens. One component occurred during the stimulation (former-response) and the other component occurred after stimulation had ceased (after-response), with a distinct tension fall between these two responses. 2. The effects of stimulation frequency and duration upon these components were examined. 3. Prazosin (0.05-0.5 microM) suppressed both responses, whereas nifedipine (0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1996
1996
1996
1996

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Alhave been widely used to investigate peripheral adrenergic though recent studies have demonstrated that, in the rat, the mechanisms (Saxena, 1970;Swedin, 1971;Anstey & Birming-cauda epididymis contains postjunctional a,-, but not OC2-ham, 1978;1980;Fukushi et al, 1988;Eltze & Boer, 1992; adrenoceptors (Ventura & Pennefather, 1991;, there is no Bultman et al, 1994). Many studies have demonstrated that, in evidence indicating which a-adrenoceptor subtypes mediate the rat, this tissue contains a functionally predominant popucontractile responses of the cauda epididymis of the guinealation of OCIA-adrenoceptors (Mallard et al, 1992;Ohmura et pig.…”
Section: Introductionmentioning
confidence: 99%
“…Alhave been widely used to investigate peripheral adrenergic though recent studies have demonstrated that, in the rat, the mechanisms (Saxena, 1970;Swedin, 1971;Anstey & Birming-cauda epididymis contains postjunctional a,-, but not OC2-ham, 1978;1980;Fukushi et al, 1988;Eltze & Boer, 1992; adrenoceptors (Ventura & Pennefather, 1991;, there is no Bultman et al, 1994). Many studies have demonstrated that, in evidence indicating which a-adrenoceptor subtypes mediate the rat, this tissue contains a functionally predominant popucontractile responses of the cauda epididymis of the guinealation of OCIA-adrenoceptors (Mallard et al, 1992;Ohmura et pig.…”
Section: Introductionmentioning
confidence: 99%